Innovative Governance Dalam Penerapan Eazy Passport Sebagai Upaya Peningkatan Kualitas Pelayanan di Kantor Imigrasi Kelas I TPI Denpasar - Saraswati, Devi Suthasih; Prabawati, Ni Putu Anik; Yudharta, I Putu Dharmanu (Lenggogeni Data Publishing, 2025)
The purpose of this research is to analyze Innovative Governance in the implementation of the Eazy Passport service as an effort to improve service quality at the Class I Immigration Office TPI Denpasar. The research method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. Based on the field research results, the analysis is conducted using Bugge's success factor theory, which consists of: (1) Governance and Innovation, (2) Innovation Culture, (3) Capabilities and Tools, (4) Sources of Ideas for Innovation, (5) Objectives, Outcomes, Drivers, and Troubles, and (6) Collecting Innovation Data for Single Innovation. The research results show that the implementation of Innovative Governance in the Eazy Passport service at the Denpasar Immigration Office has been carried out in a structured manner and has shown an improvement in quality. However, in terms of technical aspects and implementation, there are deficiencies in optimizing the Eazy Passport service. Some of these shortcomings can be linked to the success factor indicators according to Bugge, which include: Governance and Innovation, where there is a discrepancy between the minimum number of participants required in the SOP and the implementation of the Eazy Passport service; Objectives, Outcomes, Drivers, and Troubles, where there is a lack of human resources, limited service quotas, and geographical constraints. Recommendations for these issues include optimizing the Eazy Passport service quota and increasing the number of human resources. Tujuan penelitian ini adalah menganalisis Innovative Governance dalam penerapan layanan Eazy Passport sebagai upaya peningkatan kualitas pelayanan di kantor imigrasi kelas I TPI Denpasar. Metode penelitian yang digunakan yaitu deskriptif kualitatif dengan teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian lapangan dikaji menggunakan teori faktor keberhasilan menurut Bugge yang terdiri dari: (1) Governance and Innovation, (2) Innovation Culture, (3) Capabilities and Tools, (4) Sources of Ideas for Innovation, (5) Objective, Outcomes, Drivers and Trouble, (6) Collecting Innovation Data for Single Innovation. Hasil penelitian menunjukan bahwa pelaksanaan Innovative Governance dalam penerapan Eazy Passport di Kantor Imigrasi Denpasar sudah dilaksanakan secara terstruktur dan menunjukkan peningkatan kualitas, namun secara teknis dan pengimplementasian dalam mengoptimalkan layanan Eazy Passport terdapat kekurangan. Beberapa kekurangan tersebut dapat peneliti kaitkan dengan indikator faktor keberhasilan menurut Bugge, yang meliputi: Governance and Innovation, terdapat ketidaksesuaian jumlah minimal peserta pada SOP dengan implementasi layanan Eazy Passport; Objectives, Outcomes, Drivers, and Troubles, terdapat kekurangan sumber daya manusia, kurangnya kuota layanan serta hambatan geografis. Rekomendasi atas permasalahan tersebut meliputi Optimalisasi Kuota Layanan Eazy Passport serta Peningkatan Jumlah Sumber Daya Manusia. Kata Kunci: Innovative Governance, Eazy Passport, Kantor Imigrasi Kelas I TPI Denpasar, Kualitas Pelayanan, Teori Faktor Keberhasilan Bugge.